Dental Caries and Oral Hygiene in School Children in the Rural Area of the Municipality of Jericó, Antioquia, 2013 (Revista Nacional de Odontología, 2013)
Introduction: The objectives of this research were to determine the prevalence and experience of dental caries among school children in the rural area of the municipality of Jericó (Antioquia) and to analyze oral hygiene conditions in the study population.Methods: A descriptive study was carried out based on information from 534 clinical records of people between the ages of 6 and 22, with mixed and/or permanent dentitions located in the study area. We analyzed Socio-demographic, Simplified Oral Hygiene Index (ihos from the Spanish acronym), prevalence and experience of dental cavities in permanent dentition using the traditional and modified dmtf Index (dmtfT - dmtfM) and the Significant Caries Index (sic). Univariate and bivariate analyses were conducted and a Chi square test was performed to observe statistically significant differences between the variables.Results: the prevalence of dental caries including non-cavitated lesions is 39% among both genders; dental caries had been experienced by 47% of the men and 46% of the women. Taking into account the sic, the mean is 2.70 when based on the dtmfT and 4.36 on the dtmfM. These indicators are lower in women (2.56 and 3.36, respectively). The mean for the ihos is lower among women (1.25 95%ci 1.18-1.32), with statistically significant differences compared to men (p< 0.001). Differences in frequencies were observed in the dental caries and oral hygiene indicators according to age and level of education.Conclusion: Although the indicators are in accordance with international goals, inequalities were found among certain population groups.
Keywords: dental caries; scholars; oral hygiene; dmtf index; significant caries index.